Positional plagiocephaly: results of the osteopathic treatment of 424 infants. An observational retrospective cohort study - Raffaella Panza; Filippo Piarulli; Valentina Rizzo; Federico Schettini; Maria Elisabetta Baldassarre; Antonio Di Lorenzo; Silvio Tafuri; Nicola Laforgia (BMC, 2024)
Abstract Background Positional plagiocephaly is an asymmetrical flattened skull deformity whose incidence increased significantly in the last decades. Osteopathic treatment has been suggested to tackle early deformational sequences, in order to ensure the correct development of the child. The aim of the study was to assess the effectiveness of osteopathic treatment of positional cranial deformities in infants. Methods Retrospective observational study carried out at the Section of Neonatology and Neonatal Intensive Care Unit of the Department of Interdisciplinary Medicine of University of Bari, Italy in collaboration with a specialized pediatric osteopath. Results 424 infants were enrolled. Isolated positional plagiocephaly affected the vast majority of infants (n. 390, 91.98%); 34 patients (8.02%) were diagnosed with positional brachycephaly. Both infant groups (positional plagiocephaly and positional brachycephaly) had a median severity score of 3 (IQR: 3 - 3 and 2 - 3, respectively) and benefited from a median of 3 osteopathic sessions (IQR 3-4 and 2-4, respectively). Higher severity scores of positional asymmetries were significantly more common in preterm neonates (Pearson chi2: 11.58; p-value: 0.021) and in males (Pearson chi2: 10.06; p-value: 0.039). Conclusions Significant improvements in positional cranial deformations of children were obtained after only five osteopathic treatments provided in the first months of life. The osteopathic treatment could positively impact the clinical history of patients with positional plagiocephaly and positional brachycephaly. Implication for practice • Positional plagiocephaly is increasingly common among infants and may cause moderate to severe neurodevelopmental adverse effects. • Osteopathic treatment may tackle early deformational sequences, in order to ensure the correct development of the child. • Our study reveals that cranial asymmetry of infants with positional plagiocephaly is significantly reduced after only five osteopathic treatments provided in the first months of life. • Osteopathic treatment should be offered as a first line approach to young infants diagnosed with positional plagiocephaly.